2021
DOI: 10.1109/tvcg.2019.2936810
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Manifold Learning for Human Motions via Long-Horizon Modeling

Abstract: Data-driven modeling of human motions is ubiquitous in computer graphics and computer vision applications, such as synthesizing realistic motions or recognizing actions. Recent research has shown that such problems can be approached by learning a natural motion manifold using deep learning on a large amount data, to address the shortcomings of traditional data-driven approaches. However, previous deep learning methods can be sub-optimal for two reasons. First, the skeletal information has not been fully utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 46 publications
1
94
0
Order By: Relevance
“…We use a 8 to 20-frame motion prefix to start motion generation to get 900 frames (dfn_run2box_2char and dfn_boxing_3char in the video). The motion stability indicates that DFN does not suffer from the problem of cumulative error that is common in time-series generation [41]. Given the same prefix, the diversity is shown in their transitions between different postures (short-term) and different actions (long-term).…”
Section: Open-loop Motion Generationmentioning
confidence: 98%
See 3 more Smart Citations
“…We use a 8 to 20-frame motion prefix to start motion generation to get 900 frames (dfn_run2box_2char and dfn_boxing_3char in the video). The motion stability indicates that DFN does not suffer from the problem of cumulative error that is common in time-series generation [41]. Given the same prefix, the diversity is shown in their transitions between different postures (short-term) and different actions (long-term).…”
Section: Open-loop Motion Generationmentioning
confidence: 98%
“…Despite the improved accuracy and lowered costs of motion capture systems, it is still highly desirable to make full use of existing data to generate diversified new data. One key challenge in motion generation is the dynamics modelling, where it has been shown that a latent space can be found due to the high coordination of body motions [21,36,41]. However, as much as the spatial aspect is studied, dynamics modelling, especially with the aim of diversified motion generation, still remains to be an open problem.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhou et al [36] proposed a new recurrent neural network to synthesize arbitrary motions with highly complex styles. Wang et al [33] included the concept of temporal prediction in recurrent neural network to create a more stable motion manifold. Lee et al [21] synthesized human-object interaction by introducing motion grammar, a syntax to describe interaction, into a deep neural network.…”
Section: Related Workmentioning
confidence: 99%